PENINGKATAN HASIL BELAJAR MAHASISWA DENGAN MODEL PEMBELAJARAN GUIDED DISCOVERY LEARNING PADA MATAKULIAH MATEMATIKA EKONOMI - Antonius KAP Simbolon (Nusantara Hasana Journal, 2024)
The purpose of this study is to improve student learning outcomes through guided discovery learning. The research approach used is qualitative Classroom Action Research. The research was carried out with the following steps: conducting problem analysis, literature study, research implementation, data analysis, conclusions and reporting. The subjects of this study were one class of accounting study program students totaling 33. The results of the study showed that by using guided discovery learning, the number of students who obtained a minimum passing grade in the second cycle increased compared to the number of students who obtained a minimum passing grade in the first cycle. The increase in the number of students who obtained grades above the set value, which is 75, was 27% or 9 students. The research findings did not show a significant increase in student learning outcomes, but based on observations by observers and researchers, students showed a good response and collaborative attitude in group activities in the implementation of guided discovery learning.